2018
DOI: 10.4322/col.2018.003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de qualidade de vida e depressão em pacientes oncológicos e em seus cuidadores e o acesso dos pacientes a reabilitação

Abstract: Financiamento: CEPHO (Centro de Estudos e Pesquisa em Hematologia e Oncologia) Conflito de interesse: Todos os autores responsabilizam-se pelo conteúdo do presente estudo e negam conflitos de interesse que possam ter influenciado os resultados deste trabalho. Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…However, Bernardes et al (2019) and Monteiro et al (2018) reported that both the level of anxiety and depression are higher in caregivers whose respective patients have lowered mood. In addition, companions tend to have symptoms of depressed mood.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bernardes et al (2019) and Monteiro et al (2018) reported that both the level of anxiety and depression are higher in caregivers whose respective patients have lowered mood. In addition, companions tend to have symptoms of depressed mood.…”
Section: Discussionmentioning
confidence: 99%